Seasonal Changes in Locomotor Activity Patterns of Wild Social Natal Mole-Rats (Cryptomys hottentotus natalensis) - Finn, Kyle T.; Janse van Vuuren, Andries K.; Hart, Daniel W.; Süess, Tobias; Zöttl, Markus; Bennett, Nigel C. (Frontiers in Ecology and Evolution, 2022)
Differences in individual locomotor activity patterns may be linked to a number of ecological factors, such as changes in ambient temperature or photoperiod. Observations on subterranean mammals suggest that they exhibit diel rhythms despite the lack of visual cues in their underground burrows, but it is unknown how seasonality and individual characteristics affects their activity. In this study we use RFID technology to monitor daily activity patterns of wild, social Natal mole-rats (Cryptomys hottentotus natalensis) during the summer and winter to investigate how their activity varies with season and whether their activity depends on individual characteristics such as body mass, sex and reproductive status. We found that in winter, individuals were more active during the time with the highest soil temperatures, whereas in summer, they showed a bimodal activity pattern during early morning and late afternoon coinciding with cooler soil temperatures. Individual characteristics, including reproductive status, did not affect general activity indicating that reproductive and non-reproductive individuals contribute equally to cooperative behaviors. We suggest that the activity patterns may be a behavioral adaptation to avoid extreme burrow temperatures and a mechanism to maintain a stable core body temperature. We highlight the advantages of RFID technology to study wild small mammal movements.